2023
DOI: 10.4308/hjb.30.6.1149-1154
|View full text |Cite
|
Sign up to set email alerts
|

The Benthic Foraminiferal Assemblages in the Seagrass Bed of Tanjung Berakit Waters, Bintan Island

Suhartati M. Natsir,
Ira Dillenia

Abstract: Seagrass is the most common ecosystem in Tanjung Berakit waters. Therefore, Tanjung Berakit waters have a very important role as a benthic foraminiferal habitat. This study was conducted to describe the distribution of benthic foraminifera relating to the environmental condition of the waters. The samples were collected from eight stations by handling garb in November 2017. This study collected 18 species of shallow water benthic foraminifera dominated by Amphistegina and Heterostegina. This study recorded a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…Strombidae is one of the most familiar molluscan groups composed of about 100 species that mostly live in sand, seagrass, and mud flats area, and they are considered the source of food in many tropical and subtropical regions all over the world (Oo 2018;Ardila et al 2020). However, Strombidae is affected by overexploitation caused by both natural and anthropogenic stressors, which leads to a large Natsir and Dillenia 2023). On the other hand, the other study in Zamboanga del Norte and Misamis Occidental, Philippines, showed that the most abundant species found in the selected area is the Canarium esculentum with 33.25% species, followed by the Canarium urceus with 17.49%, and the majority of the Strombidae species are found in the sandy-muddy substrate (Pangarungan et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Strombidae is one of the most familiar molluscan groups composed of about 100 species that mostly live in sand, seagrass, and mud flats area, and they are considered the source of food in many tropical and subtropical regions all over the world (Oo 2018;Ardila et al 2020). However, Strombidae is affected by overexploitation caused by both natural and anthropogenic stressors, which leads to a large Natsir and Dillenia 2023). On the other hand, the other study in Zamboanga del Norte and Misamis Occidental, Philippines, showed that the most abundant species found in the selected area is the Canarium esculentum with 33.25% species, followed by the Canarium urceus with 17.49%, and the majority of the Strombidae species are found in the sandy-muddy substrate (Pangarungan et al 2022).…”
Section: Discussionmentioning
confidence: 99%